The comparison of two different mandibular positions for oral appliance therapy in patients with obstructive sleep apnea - Eri Makihara; Takafumi Watanabe; Hiromichi Ogusu; Shin‐Ichi Masumi (Wiley, 2022)
Abstract Background An oral appliance (OA) can alleviate upper airway obstruction by pulling the mandible forward during sleep. While a large mandibular advancement with an OA decreases the number of apnea and hypopnea events, long‐term use may cause side effects, such as toothache, stiffness, and pain in the temporomandibular joint. Objetives This study aimed to evaluate the effectiveness of different mandibular positions for obstructive sleep apnea (OSA) and determine the optimal therapeutic mandibular position. Methods Thirty‐two patients (17 males and 15 females) with mild to moderate OSA participated in this prospective study. All patients were randomly allocated to receive a 50% mandibular advancement or a 75% mandibular advancement with an OA. The pre‐ and posttreatment apnea‐hypopnea index (AHI), apnea index (AI), and Epworth Sleepiness Scale (ESS) were compared. Treatment effectiveness and treatment success were compared between groups. Results AHI improved significantly in both groups, and AI improved significantly in the group with 50% mandibular advancement. No significant improvements in the ESS were observed in either group. There was no significant difference in treatment effectiveness between groups. In the proportion of females and males whose treatment was effective in the two groups, females were significantly greater than males. Conclusions For patients with mild to moderate OSA, 50% mandibular advancement is recommended as the initial therapeutic mandibular position. It was suggested that gender differences also affect treatment effectiveness.